Framing the Global Landscape of Entrepreneurship Education and Training Programs - World Bank (Washington, DC, 2014)
Entrepreneurship is of fundamental importance as a catalyst for innovation, job creation, and economic well-being. Policymakers have a strong interest in promoting entrepreneurship given that its development is necessary for fighting poverty and unemployment. This paper is an initial contribution to help fill gap, performing a systematic review of Entrepreneurship Education and Training (EET) programs worldwide and developing a conceptual framework that is applied to systematically analyze EET programs. The objective of this framework paper is to identify the dimensions of EET programs that matter for realizing the spectrum of EET-related outcomes. To meet that objective, the paper presents a conceptual framework and applies it to systematically analyze effective EET programs. The aim is to find common practices and trends across effective programs and draw from them practical insights of value to future EET program design and implementation. This framework paper is organized into four parts: part one summarizes major findings and trends from a review of EET research and provides definitions to distinguish between Entrepreneurship Education (EE) and Entrepreneurship Training (ET). Part two outlines the conceptual framework that emerged from the review of EET research. Part three analyzes the global landscape of EET programs by target group and provides findings from that analysis. Part four summarizes the study's findings, presents a roadmap for investment and policy decisions related to EET, and proposes areas for further research.